MNC ON OIL AND GAS EXPLORATION: ExxonMobil Gas and Oil Exploration in The Spratly Islands - Adi Mustofa (: 2621-0924)
as. Abstract  The role of MNCs in the current of international political process should not be underestimated, since it has a very decisive role in the new development is characterized by the emergence of non-state actors who play a vital role in the economy of engagement across borders. ExxonMobil is one of the US-owned MNCs based energy engaged in the oil and gas, which are implisist is discussed in this study. The energy sector as oil and gas operations of the most fertile land for the MNCs, because oil and gas were the sectors most determine the course of the world economy. should be know that ExxonMobil conducts exploration in the Spratly Islands which as a region of strategic and rich in natural resources. Along with the abundant wealth of natural resources such as oil and gas in the Spratly Islands, have an impact on neighboring countries, where they want to exploit energy resources in the Spratlys to support the country's economy. The methodology used in this study is an analytical deductive method, That means research that has a purpose to provide an explanation of the reality on the object studied in an objective and comprehensive. This study is also based on an Islamic worldview. While the data collection methods used by library research, is to find a variety of information, news analysis, concepts of the ideas of experts published in books, journals, articles, internet, and print media relating to the theme. However, ExxonMobil should not miss its opportunity to explore in the Spratly, because  by doing the exploration, Exxonmobil can get the profit as much as possible and can build its image by expantion to the Spratly region. Keywords : MNCs, ExxonMobil, Spratly, Oil and Gas.